The cascade of global trade to large climate forcing over the Tibetan Plateau glaciers - Kan Yi (Nature Portfolio, 2019)
To trace the sources of Black Carbon being transported into the Tibetan Plateau is crucial for guiding an effective mitigation strategy. Here the authors utilized the adjoint of the Goddard Earth Observing System-Chem model and find that international trade aggravates the BC pollution over the HTP glacier regions and may cause significant climate change.